The relationship between shoulder joint response with cervical multifidus muscle dimensions. (April 2018) - Kian-Bostanabad, Sharareh; Azghani, Mahmood-reza; Rahnama, Leila
Abstract: Deep cervical muscles play an important role in creating neck stability. Several changes in muscles function have been observed in people with neck pain. With regard to the problems of recording activity of cervical multifidus muscle with EMG, ultrasound has been used to evaluate the activity of this muscle. Purpose of this paper is investigation the effect of shoulder joint activities on the cervical multifidus muscle thickness changes in people with and without neck pain and providing predictive models by response surface methodology for the relationship between this factors. So, after data clustering in two groups of over 50% and less than 50% of maximum voluntary contraction (MVC), predictive models for each subjects, two groups, both left and right sides and six activities calculated. R 2 (regression correlation coefficient) values of the resulting models in healthy subjects and people with neck pain are between 0.24–0.96 and 0.09–0.87, respectively. By assessing the resulting models, it seems that assessment the thickness of this muscle in the dominant hand side during shoulder abduction activity in the strength of 0–50% MVC for healthy subjects and 50–100% MVC for people with neck pain can be an appropriate factor for evaluation the behavior of this muscle.